The Influence of Total Assets and Sales Volume Through Net Profit on Stock Prices in the Pharmaceutical Sub-Sector Listed on the Indonesian Stock Exchange Period 2016-2022 - Artati, Susi (Journal of Accounting and Finance Management, 2024)
Investors are interested in buying shares because they have high profit expectations, even though the risk is also high. Stocks have the potential to generate very high returns in the long term, especially shares of fast-growing companies. This research aims to determine and analyze the influence of total assets and volume simultaneous or partial sales on net profit, knowing and analyzing the influence of total assets and volume simultaneous or partial sales on share prices, and to determine and analyze the effect of net profit on stock price in the pharmaceutical Sub Sector listed on the Indonesia Stock Exchange for the 2018–2022 period. This research method is quantitative and descriptive, using path analysis. Research data was obtained from secondary data in the form of annual financial reports for each company in the pharmaceutical Sub Sector listed on the Indonesia Stock Exchange for 2018–2022. Statistical analysis was carried out using the SPSS program. The conclusions of this research are: 1) Total assets and sales volume simultaneously have a positive effect and are significant to share prices in pharmaceutical Sub Sector companies listed on the Indonesian Stock Exchange for the 2018–2022 period. 2) Total assets and sales volume simultaneously have a positive and significant effect on net profit in pharmaceutical Sub Sector companies listed on the Indonesia Stock Exchange for the 2018–2022 period. 3) Total assets partially have a positive and significant effect on profit net in pharmaceutical Sub Sector companies listed on the Stock Exchange Indonesia for the 2018–2022 period. Sales volume is partially influential and significant on net profit in Sub Sector pharmaceutical companies listed on the Indonesian Stock Exchange for the 2018–2022 period. 4) Total assets partially have a positive and significant effect on prices and shares of pharmaceutical Sub Sector companies listed on the Stock Exchange of Indonesia for the 2018–2022 period. Sales volume partially has a negative and significant effect on share prices in Sub Sector pharmaceutical companies listed on the Indonesian Stock Exchange for the 2018–2022 period. 5) Net profit has a positive and significant effect on share prices for pharmaceutical Sub Sector companies listed on the Indonesia Stock Exchange for the 2018–2022 period.